2021
DOI: 10.1155/2021/6630272
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Shigellosis among Children Aged below Five Years with Diarrhea at Banadir Hospital in Mogadishu, Somalia

Abstract: Globally, shigellosis remains the second leading cause of diarrhea-associated deaths among children under five years of age, and the infections are disproportionately higher in resource-limited settings due to overcrowding, poor sanitation, and inadequate safe drinking water. The emergence and global spread of multidrug-resistant (MDR) Shigella are exacerbating the shigellosis burden. We adopted a cross-sectional study design to determine the distribution and antimicrobial susceptibility (AST) patterns of Shig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Another study conducted in -Treatments need to be based on species identifcation [26] Table 1: Continued. -Among the serogroups, most of the MDR phenotypes were found in S. fexneri (65.9%) Tere is an urgent need for AMR surveillance and continuous monitoring [32] Note: "-" means not done or did not get the information. Somalia [32] showed the highest resistance to ceftriaxone occurred among S. sonnei (66.7%) serogroup, followed by S. dysenteriae type 1 (40%) and S. fexneri (38.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted in -Treatments need to be based on species identifcation [26] Table 1: Continued. -Among the serogroups, most of the MDR phenotypes were found in S. fexneri (65.9%) Tere is an urgent need for AMR surveillance and continuous monitoring [32] Note: "-" means not done or did not get the information. Somalia [32] showed the highest resistance to ceftriaxone occurred among S. sonnei (66.7%) serogroup, followed by S. dysenteriae type 1 (40%) and S. fexneri (38.5%).…”
Section: Discussionmentioning
confidence: 99%
“…-Among the serogroups, most of the MDR phenotypes were found in S. fexneri (65.9%) Tere is an urgent need for AMR surveillance and continuous monitoring [32] Note: "-" means not done or did not get the information. Somalia [32] showed the highest resistance to ceftriaxone occurred among S. sonnei (66.7%) serogroup, followed by S. dysenteriae type 1 (40%) and S. fexneri (38.5%). In this review, included studies primarily used stool culture for Shigella identifcation.…”
Section: Discussionmentioning
confidence: 99%
“…Shigella causes an infection known as shigellosis. Most infected individuals develop fever, diarrhoea, and stomach cramps, but often recover without chemotherapeutic interventions ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further WGSA of the GEMS study isolates showed multiple Phylogroups of S. flexneri in each participating African country, highlighting the diversity of circulating strains [16]. While this provides a useful snapshot into the diversity of Shigella strains circulating regionally, detailed national studies are needed to further unpick the ecology of shigellosis in the region.Non-genomic studies from across sub-Saharan Africa highlight the importance of endemic disease in the region and confirm S. flexneri is typically the dominant serogroup of Shigella [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. There is variation in shigellosis incidence, sub-continentally and nationally, with national attributable disease burden estimates of up to 63.3% of diarrhoeal cases, and intra-national variation as high as 34% [46,47].…”
mentioning
confidence: 99%
“…Non-genomic studies from across sub-Saharan Africa highlight the importance of endemic disease in the region and confirm S. flexneri is typically the dominant serogroup of Shigella [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. There is variation in shigellosis incidence, sub-continentally and nationally, with national attributable disease burden estimates of up to 63.3% of diarrhoeal cases, and intra-national variation as high as 34% [46,47].…”
mentioning
confidence: 99%